Predicting Grip Angle Using Some Kinematical Variables Of Leaving and Flight In Parallel Bar In Men’s Gymnastics (Qatar 2016) - Ngah, Yessar (Journal of Physical Education, 2017)
The problem of the research lies in the motor analysis of Tores Skill phase on parallel bar during leaving and flight using grip angle as an indicator. The aim of the research was to identify the effect of grip angle on the performance on parallel bar and the relationship between them. The researcher used the descriptive method. The subjects were (4) gymnasts who participated Qatar Championship 2016. The data was collected and treated using proper statistical operations. The researcher concluded a prediction formula for grip angle that can be used by researchers for comparative studies.